2023
DOI: 10.1590/1517-7076-rmat-2023-0201
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of asphalt mixtures containing reclaimed asphalt incorporating Acrylonitrile Butadiene Styrene (ABS)

Kamalasekar Athiappan,
Rajiah Murugasan,
Chandrakasu Makendran
et al.

Abstract: Huge accumulations of Recycled asphalt pavement (RAP), scarcity of bitumen obtained from natural resources, RAP causing environmental pollution, and increased construction of flexible pavement all over the world led the researchers to reuse the improved aged bitumen by modifiers. Hence, in this research, the reclaimed aged asphalt improved by ABS (5% weight of virgin bitumen) was partially replaced by virgin bitumen (10 to 60% with an increment of 10%) used in the asphalt mix, and mechanical properties such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…In the second deposition step (475 to 600 ºC), this is associated with the end of the degradation of acrylonitrile. It was observed that between ~ 200 ºC and 325 ºC other decompositions occur; however, the reactions involved are volatiles that exist in the ABS [36][37][38], similar observations are also described in the literature [39][40][41][42].…”
Section: Thermogravimetric and Calorimetric Analysis (Tga/dsc)supporting
confidence: 80%
“…In the second deposition step (475 to 600 ºC), this is associated with the end of the degradation of acrylonitrile. It was observed that between ~ 200 ºC and 325 ºC other decompositions occur; however, the reactions involved are volatiles that exist in the ABS [36][37][38], similar observations are also described in the literature [39][40][41][42].…”
Section: Thermogravimetric and Calorimetric Analysis (Tga/dsc)supporting
confidence: 80%
“…In addition to these, several other polymeric materials have shown promise. For example, the use of acrylonitrile butadiene styrene (ABS) plastic, known for its toughness and impact resistance, in asphalt mixtures can potentially enhance road durability in high-traffic areas [ 31 , 32 ]. Furthermore, research into utilizing polylactic acid (PLA), a biodegradable plastic, suggests that it could be used to increase the environmental sustainability of road infrastructures [ 33 ].…”
Section: Introductionmentioning
confidence: 99%